The no-nonsense guide to equality - Dorling, D (New Internationalist, 2012)
A wide-ranging exploration of why inequality persists and what can be done about it. The No-Nonsense Guide to Equality discusses the positive effects that equality can have, using examples and case studies from across the globe, including many from the UK. It examines the lessons of history and covers race, gender and ethnicity, age, and wealth. Danny Dorling considers, realistically, just how equal it is possible to be, the challenges we face, and the factors that will lead to greater equality for all.